Megaprepuce: presentation of a modified surgical technique with excellent cosmetic and functional results - Hirsch, K.; Schwaiger, Brigitte; Kraske, S.; Wullich, Bernd (Journal of Pediatric Urology, 2019)
Objective: Congenital megaprepuce is a malformation consisting of a great redundancy of the inner preputial skin over a penis with normal shaft and glans and is combined with a severe phimosis. Patients suffer from difficulties in voiding because the urine is trapped in the large dome-shaped megaprepuce. We describe a modification of the surgical technique of reconstructing a megaprepuce initially presented by Leao et al. Patients and methods: We retrospectively reviewed 7 patients aged 6–53 months (mean age 17 months, 6 were younger than 18 months) who underwent congenital megaprepuce repair between 02/2014 and 05/2018 in our institution. All these otherwise healthy children suffering from difficulties in voiding and reporting genital ballooning during micturition and urinary retention were referred to our hospital. In all cases, parents needed to express the trapped urine. Four of these patients additionally showed a glanular hypospadias, another one a distal penile hypospadias. In addition to the repair of the megaprepuce, six patients needed correction of a penile curvature, five of whom needed correction of the chordee and one a corporoplasty (Schröder-Essed). The patient showing the distal penile hypospadias additionally underwent hypospadias repair. During the follow-up, we evaluated the cosmetic result and complications such as secondary concealed penis, difficulties in voiding, urinary retention, and urinary infections. Results: Mean follow-up was 18 months. All patients following surgery showed normal voiding without urinary retention or urinary infections and good cosmetic results resembling a circumcised penis in appearance without reconcealment. No intraoperative complications occurred. One patient had a scrotal hematoma postoperatively. Mild transient edema of the penis was seen in all patients, which disappeared spontaneously within one week after surgery. Conclusion: Our surgical approach is a safe and relatively simple procedure with a low rate of complications, good cosmetic results, and functional outcome. Whether the hypospadias associated with ventral curvature was a coincidence or part of the disease pattern remains unclear but will probably be the object of further investigations.[Figure presented]
CRIS-Team Scopus Importer:2019-07-16
Keywords: Hypospadias; Megaprepuce; Modified surgical technique

Renal transplantation: Opportunities and risks for medical refugees - Mammadova, Dilbar; Hirsch, K.; Schwaiger, Brigitte; Wullich, Bernd; Rascher, Wolfgang (Urologe, 2018)
BACKGROUND: Families with children and adolescents with end-stage renal disease came to Germany from the former Eastern Bloc countries before the wave of refugees in 2015, in order to enable their children to survive with adequate kidney replacement therapy and in the best case a kidney transplant. METHODS: In a case study, medical records of 4 childen and adolescents were retrospectively analyzed. These patients who fled to Germany for the treatment of terminal renal failure applied for asylum and were successfully transplanted after the usual waiting period. RESULTS: Four of the eight children and adolescents who came to Erlangen for treatment of terminal renal failure between 2003 and 2013 received a functioning kidney transplant (deceased donor kidney) after dialysis therapy was difficult due to lack of compliance to drug and dietary recommendations such as fluid restriction. Since children and adolescents are treated with chronic dialysis only with the aim of kidney transplantation, a living donation was discussed but was not possible for medical reasons. 3 recipients are symptom-free with a functional graft. DISCUSSION: The case study demonstrates that children and adolescents fleeing to Germany due to their end stage renal disease are better integrated after kidney transplantation, have better chances of obtaining a good education and can be expected to live independently with their own income in the future.
EVALuna2:35726

Robot-assisted laparoscopic pyeloplasty in adults: Excellent long-term results of primary pyeloplasty - Traumann, M.; Kluth, L. A.; Schmid, M.; Meyer, C.; Schwaiger, Brigitte; Rosenbaum, C.; Schriefer, P.; Fisch, M.; Dahlem, R.; Seiler, D.; Ahyai, S.; Haese, A.; et al. (Urologe, 2015)
With the development of the robot-assisted surgical technique, robot-assisted pyeloplasty (RAP) has become established as an alternative to open and laparoscopic surgery. Currently there are only a few single-center studies with larger numbers of cases and long-term results. The aim of this study was to investigate perioperative and long-term postoperative success rates of Anderson-Hynes robot-assisted pyeloplasty (RAP) at a single center.We retrospectively reviewed our RAP experience of 61 patients performed by two surgeons between 2004 and 2013 regarding operating time, length of hospital stay, perioperative complication, and success. Overall success was measured in terms of necessary redo pyeloplasty. We also identified patients with temporary stent placement due to symptomatic hydronephrosis or with further obstruction in diuretic renography.Median age, operating time, and follow-up were 33 years, 195 min, and 64 months, respectively. No conversion to open procedure was necessary. The success rate was 98% (n=60) with 1 patient undergoing open redo pyeloplasty due to a recurrent stenosis. Temporary stent placement was required in 3 patients due to pyelonephritis and dilatation.Satisfying long-term success rates including low complication rates of RAP were obtained in this study. RAP presents a safe and standardized procedure for symptomatic ureteropelvic junction obstruction.
EVALuna2:16306